2020
DOI: 10.1111/jfd.13153
|View full text |Cite
|
Sign up to set email alerts
|

A novel research on isolation and characterization of Photobacterium damselae subsp. damselae from Pacific white shrimp, Penaeus vannamei, displaying black gill disease cultured in China

Abstract: In June 2019, massive mortalities of cultured Penaeus vannamei occurred in a local farm in Hainan Province, China. The diseased shrimp displayed evident black gills.Three bacterial strains 20190611001, 20190611007 and 20190611022 were isolated from hepatopancreas and gills of the diseased shrimp and identified as Photobacterium damselae subsp. damselae based on the sequence analysis of 16S rRNA and toxR genes. These three isolates showed haemolytic activities. Of them, strain 20190611022 isolated from hepatopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…In the liver, we found that hepatocytes were swollen by light microscopy and this attributed to glycogen infiltration and few fat globule depositions. These findings were similar to previous studies on Pacific white leg shrimp, Litopenaeus vannamei shrimp, where the hepatopancreas was mostly affected with P. damesale (Singaravel et al., 2020; Wang et al., 2020). Although there were no bacteria seen by light microscopy in experimentally infected fish, one bacterium was seen inside the phagosome of phagocytic cells by transmission electron microscopy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the liver, we found that hepatocytes were swollen by light microscopy and this attributed to glycogen infiltration and few fat globule depositions. These findings were similar to previous studies on Pacific white leg shrimp, Litopenaeus vannamei shrimp, where the hepatopancreas was mostly affected with P. damesale (Singaravel et al., 2020; Wang et al., 2020). Although there were no bacteria seen by light microscopy in experimentally infected fish, one bacterium was seen inside the phagosome of phagocytic cells by transmission electron microscopy.…”
Section: Discussionsupporting
confidence: 92%
“…The isolated P. damselae was highly sensitive to chloramphenicol and doxycycline, whereas it was partially sensitive to florfenicol, ciprofloxacin and norfloxacin. It has been reported previously that Phdd is susceptible to norfloxacin and chloramphenicol (Wang, Yue, Lu, & Liu, 2013; Wang et al., 2020). In addition, both subspecies of P. damselae were sensitive to florfenicol and ciprofloxacin (Abdel‐Aziz et al., 2013; Habiba et al., 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Proteobacteria do not change in abundance with environment or diet and are the most stable bacteria in L. vannamei, while the abundance of the other major bacterial phyla (Firmicutes, Bacteroidetes, Actinobacteria) may vary with developmental stage, diet, and environmental factors (Li et al, 2018). At the genus level, Vibrio and Photobacterium are known as opportunistic pathogens and have been reported in shrimp diseases (Avendaño-Herrera et al, 2006;Liu and Qiu, 2007;Wang et al, 2020). Tenacibaculum and Acinetobacter have also been reported as bacterial pathogens, while the former was identified in marine fish, which causes an ulcerative disease (Avendaño-Herrera et al, 2006) as well as the latter was identified as a potential pathogen of red leg disease in the Pacific white shrimp (Huang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…By taking into account the black gill disease case as an example, our results revealed that the diseased shrimp was infected by multiple pathogenic agents, such as P. damselae subsp. damselae (Wang, Shi, et al, 2020) and it is accordingly suggested that V. brasiliensis might be involved in the secondary infections. Previous reports showed that the environmental stress factors, such as elevated temperature, oxygen deficiency and high concentrations of ammonia, lead to the increased susceptibility for shrimp to infective pathogens (Chang et al, 2015;Liu & Chen, 2004;Sung et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the challenge tests, shrimp were divided among 10-litre plastic tanks, each containing 10 shrimp. Shrimp were challenged via reverse gavage with different bacterial suspensions, according to the methodology previously described by Tran et al (2013) and Wang, Shi, et al (2020). The concentrated bacterial cells were resuspended in PBS and adjusted to the concentration of 1.01 × 10 9 CFU/ml.…”
Section: Experimental Challenge Testmentioning
confidence: 99%